Online optical monitoring system for analyzing the surface discharge signal - 293472 Wong, Soo Mean (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1999